STANDAR AKUNTANSI KEUANGAN DAN PRAKTIK MANAJEMEN LABA DI INDONESIA - Eni Indriani; Rahmi Sri Ramadhani; Widia Astuti (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
Financial reporting in Indonesia is based on accrual-based Financial Accounting Standards (SAK), where according to Watts and Zimmerman (1986) accounting recorded on an accrual basis is subject to managerial discretion, due to the flexibility given by the General Accepting Accounting Principle (GAAP), which gives managers encouragement to modify financial statements (earnings management). This study aims to map earnings management practices in Indonesia after convergent Financial Accounting Standards on IFRS. The data analysis technique used in this study is the two different test average with the t-test (independent sample t-test). The results of data analysis found that there were no significant differences. This is caused by the same earnings management pattern. The highest level of earnings management implementation exists in countries with weaker legal institutions and higher levels of pre-transition earnings management, which are partially and fully associated with market value and returns, which means that earnings management practices continue to be carried out because market demands for high rates of return on investment.